Negotiating motherhood and authority: the experience of non-migrant wives in parenting their adolescent children from Filipino transnational families - Domingo, Peachy (Frontiers in Sociology, 2025)
Transnational Filipino families arise from temporary labor migration, often with one parent abroad. This reshapes family life, impacting parent-child relationship and gender dynamics, and caregiving for children left-behind. However, non-migrant mothers’ crucial role in sustaining life and providing care is often overlooked in studies. This study examines how non-migrant wives in Filipino transnational families maintain and negotiate their authority in raising their adolescent children. This study utilized qualitative descriptive approach in conducting interviews with 20 Filipino mothers from transnational families in rural Philippines. Findings revealed that non-migrant mothers enforce their authority through various strategies such as the adoption of authoritarian parenting style, leveraging the authority of the Overseas Filipino Worker (OFW) husbands, chore delegation among adolescent children, and engage in negotiations regarding both their authority and their children’s autonomy. In examining Filipino transnational families, this study offers a novel perspective on maternal authority, situating its enforcement within the context of mothers’ significant and often equal financial contributions with their OFW husbands. This paper argues that maternal authority is profoundly shaped by the good motherhood ideology, where mothers actively promote children’s positive behavior and values as a testament to their own efficacy despite the absence of their OFW husbands. The unique contribution of this study lies in demonstrating how mothers primarily achieve this through consistent nagging and reprimanding their adolescent children. A mother’s financial contribution, relative to her husband’s remittances, significantly affects the effectiveness of her maternal control strategies and her perceived authority over their children. Furthermore, when their direct authority is insufficient, mothers strategically leverage the traditional disciplinarian role of their OFW husbands, highlighting a critical, yet under-explored, reciprocal dynamic: non-migrant wives reinforce the OFW father’s authority, while the OFW husband’s involvement simultaneously empowers the mother’s disciplinary actions. This intricate interplay of roles and financial contributions distinguishes our understanding of parental authority in transnational family structures.